Screening for glucose dysregulation in β-thalassemia major (β-TM): An update of current evidences and personal experience : Screening for glucose dysregulation in β-thalassemia major - De Sanctis, Vincenzo; Daar , Shahina; Soliman, Ashraf T; Tzoulis , Ploutarchos; Karimi , Mehran; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2022)
Abstract. Glucose dysregulation (GD) in patients with β-thalassemia major (β-TM) usually develops gradually. Prediabetes consists of two abnormalities, impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), the latter detected by a standardized oral glucose tolerance test (OGTT). Diagnosis of prediabetes is essential for an early identification of high-risk individuals who will benefit from intensive iron chelation therapy and lifestyle modification. Therefore, patients with β-TM should undergo annual screening for glucose abnormalities, according to international recommendations, starting from the age of 10 years. OGTT remains the preferred screening method as it is more sensitive for GD than fasting plasma glucose (FPG), although it is poorly reproducible. The use of HbA1c measurement has limited use as it is generally considered unreliable in patients with thalassemia. Continuous glucose monitoring system (CGMS) is an accurate method to detect the variability of glucose fluctuations and offers the opportunity for better assessment of glucose homeostasis in a selected group of β-TM patients. Pancreatic Magnetic Resonance Imaging (MRI) associated with insulin secretion-sensitivity index-2 (ISSI-2) could be a complementary test, minimizing the necessity for OGTT and identifying high-risk patients before irreversible pancreatic damage occurs. The aims of this short report are to give practical guidance for an early identification of GD in β-TM patients, to summarise our experience, and to offer an impetus for further research in the field.